Pelatihan Kewirusahaan: Punya Usaha Sendiri, Mengapa Tidak: Koperasi Serba Usaha “Aneka Usaha” Karangbendo, Kapanewon, Banguntapan Bantul - R. Nur Budi Setiawan; MG. Suwarni (Jurnal Nusantara Berbakti, 2024)
Objective to mobilize local communities to want to become entrepreneurs by developing all the potential around them, especially for members of the multi-business cooperative "Aneka Usaha" Karangbendo, Kapanewon Banguntapan Bantul. Problem there is still a low level of entrepreneurial spirit and limited knowledge about entrepreneurship, especially for members of the multi-business cooperative "Aneka Usaha", which has not been developed optimally. Method opening a mindset regarding entrepreneurship and providing motivation and practical knowledge to members of the multi-business cooperative "Aneka Usaha" by providing workshops and discussions with business people and new members who do not yet have their own business. Results: Interest in entrepreneurship among members of the multi-business cooperative "Aneka Usaha" is very high, especially for new members of the cooperative. For this reason, partnerships are needed with more established business actors and universities so that new local entrepreneurs emerge more quickly among the younger generation.